2021
DOI: 10.1016/j.jbc.2021.100494
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the resolving cysteine affects the structure and hydrogen peroxide reactivity of peroxiredoxin 2

Abstract: Peroxiredoxin 2 (Prdx2) is a thiol peroxidase with an active site Cys (C52) that reacts rapidly with H 2 O 2 and other peroxides. The sulfenic acid product condenses with the resolving Cys (C172) to form a disulfide which is recycled by thioredoxin or GSH via mixed disulfide intermediates or undergoes hyperoxidation to the sulfinic acid. C172 lies near the C terminus, outside the active site. It is not established whether structural changes in this region, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…The reason behind this is likely to be purely technical: BiFC simply cannot capture small differences in reaction rates. The slightly slower k on of the resolving cysteine mutant could be a consequence of minor local structural changes by which the efficiency of reactivity of C P is partially being compromised, as reported recently for Prdx2 [51]. The reaction of the resolving cysteine Prdx1 mutant with urate hydroperoxide was also lower than for the WT [61].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The reason behind this is likely to be purely technical: BiFC simply cannot capture small differences in reaction rates. The slightly slower k on of the resolving cysteine mutant could be a consequence of minor local structural changes by which the efficiency of reactivity of C P is partially being compromised, as reported recently for Prdx2 [51]. The reaction of the resolving cysteine Prdx1 mutant with urate hydroperoxide was also lower than for the WT [61].…”
Section: Discussionsupporting
confidence: 55%
“…This Prdx1 variant was less sensitive to hyperoxidation compared to Prdx1 WT. Peskin et al [51] also noticed this in some of the resolving cysteine mutants of Prdx2, where they showed that the rate of hyperoxidation was dramatically decreased compared to Prdx2 WT [51].…”
Section: Prdx1 Interacts With the Thioredoxin Binding Domain Of Ask1 In Vitromentioning
confidence: 87%
“…It has been shown by SEC and TEM that the AhpC from Enterococcus faecalis, a naturally Ser-Prx, is a decamer independent of the redox state [43], similarly to yeast Tsa2 [3]. Thus, our results showed that the presence of Thr or Ser in the catalytic triad is a relevant factor related to the redox sensitive oligomerization, but additional features also interfere with the quaternary assembly of typical 2-Cys Prx [43,45,61].…”
Section: Comparative Analysis Of the Inactivation Of Bacterial Thr-pr...supporting
confidence: 50%
“…In fact, our data indicated that, in yeast enzymes (displaying the GGLG/YF motifs), the differences in hyperoxidation are more pronounced between Ser-Prx and Thr-Prx. Accordingly, Peskin and colleagues (2021) [61] showed that substitution of human Prx2 C R by amino acids that disrupts the C-terminal structure is able to affect the enzyme activity, indicating an interconnection between the C-terminal region and the active site microenvironment in eukaryotes. These data indicate that even regions located far from the active site can exert effect in the 2-Cys Prx activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to unambiguously exclude that proteins no longer bind to the used peroxiredoxin mutants due to structural changes other than loss of the cysteine thiol. For the resolving cysteine mutants at least, a recent study shows that the cysteine to serine mutation has only a limited effect on the rate of oxidation of the peroxidatic cysteine in PRDX2 [32]. Characterization of the functional consequences of specific peroxiredoxinbased interactions is outside the scope of this study.…”
Section: Limitations Of This Studymentioning
confidence: 94%